Efeito do canabidiol no processo cicatricial de defeitos ósseos críticos mecanicamente induzidos em calota craniana de ratos : avaliação clínica e histológica - Noronha, Rafael de Araújo (2018)
Maxillofacial fractures of traumatic origin have a high incidence in the world population. These can be treated in different ways, ranging from conservative methods to widely invasive procedures. Among the multiple possibilities of treatment of this type of disease is the use of herbal medicines, where cannabidiol (CBD) is inserted. This is the main non-psychomimetic component of Cannabis sativa (Can-ns) and plays potent anti-inflammatory, antioxidant and analgesic effects in a variety of pathological conditions. The present dissertation is structured in the form of 2 scientific papers. The first one consists of a literature review, whose objective was to evaluate the mechanisms of action of CBD that may be involved in bone repair. The results of this study suggest that CBD is unable substance of interfering in the healing process of bone defects from its anti-inflammatory and antioxidant potential. The second is an experiment in an animal model, using 64 Wistar rats, divided into two groups (test with CBD and control). At the periods of two, four, six and eight weeks, they were evaluated clinically and histologically in the cicatricial process of mechanically induced bone defects in the skull cap of rats. It was found that the CBD exerted a beneficial effect in the fourth week after treatment where an increase in the mean of neoformed bone within the defect was observed, however, no statistically significant difference was observed in the healing process of the bone defects at the times analyzed. These results suggest the need to deepen the theme, aiming at a better understanding of the possible effects of CBD on bone metabolism and repair.